Pembiayaan Investasi Bank Syariah dan Pertumbuhan Produksi Usaha Kecil dan Menengah: Bukti Data Panel Indonesia Kawasan Barat - Khairul Amri; Cut Dian Fitri; Muhammad Adnan; Muhammad Zulhilmi; Zaki Fuad (AL-MUZARA'AH, 2022)
This study aims to examine and analyze the effect of Islamic bank investment financing on the production growth of small and medium enterprises (SMEs). Using panel data from 8 provinces in western Indonesia from 2014.Q3 to 2019.Q3, the analytical model used is the cointegration test, vector error correction model, and Granger causality test. The study found a long-term and short-term relationship between the two variables. In the long term, investment financing will positively and significantly increase SMEs' production growth. Furthermore, in the short run, the relationship between the two variables is negative. Granger causality test results indicate a two-way causality between investment financing and production index growth. Production responses to changes in investment financing and vice versa, the investment financing is also a response to changes in SMEs' production growth.